The Prevalence of Hepatitis E in a Patient Cohort Presenting With Addictive Injection Behavior - Yrondi, Antoine; Salles, Juliette; Péron, Jean Marie; Sporer, Marie; Taib, Simon; Gallini, Adeline; Noilhan, Chloé; Dimeglio, Chloé; Entajan, Flora; Crequy, Marie; Izopet, Jacques; Schmitt, Laurent (Frontiers in Psychiatry, 2019)
Introduction: Hepatitis E is the most common cause of acute viral hepatitis worldwide. Seroprevalence is approximately 15% in developed countries, and 22% in France. hepatitis E virus (HEV) can be transmitted via transfusions and therefore possibly intravenous (IV) drug use. Hepatitis E serology is routinely tested in patients who seek medical advice for addictive injection behavior at the addiction treatment, support and prevention unit of Toulouse University Hospital. We assume that hepatitis E is more prevalent in patients presenting with addictive injection behavior than in the general French population. Methods: Hepatitis E serological assays [immunoglobulin M (IgM) and IgG] were carried out for all patients presenting with addictive injection behavior during an initial evaluation. The controls were taken from a cohort of 3,353 blood donors living in southern France and who donated blood during the first 2 weeks of October 2011. Results: We included 52 patients presenting with addictive injection behavior and 103 healthy controls matched for age, sex, and area of residence. We found no difference between patients and controls for the prevalence of hepatitis E: patients vs. healthy controls: positive IgGs: 42.31%, 95% confidence interval (CI) (28.73–56.80%) vs. 43.43%, 95% CI (33.50–53.77%) (p = 0.89) and positive IgMs: 3.85%, 95% CI (0.47–13.22%) vs. 4.85%, 95% CI (0.16–10.97%) (p = 0.57). Conclusion: There was no difference in HEV seroprevalence between IV drug users and the general population, suggesting that the IV route of HEV infection is not significant in this population.